1997
DOI: 10.1007/s004210050149
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the optimal walking speed for neural relaxation in healthy elderly women using electromyogram and electroencephalogram analyses

Abstract: The purpose of this study was to determine the walking speed which has the greatest influence on neural relaxation in healthy elderly women as determined by electromyogram (EMG) and electroencephalogram (EEG) analyses. Seven elderly female volunteers [mean age 68.5 (SD 3.95) years] served as subjects for this study. The EMG signals were recorded from the gastrocnemius (MG), soleus (SL) and tibialis anterior (TA) muscles while walking on a treadmill, starting at 40 m.min-1 and increasing 6 m.min-1 incrementally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…By comparison with the alpha%-power to beta%-power, both groups showed high beta%-power during exercise and big increases of alpha%-power after exercise. This is basically consistent with other reports about the influence of exercise on alpha-beta wave (Petruzzello and Landers, 1994;Shibata et al, 1997). However, 24TJQ is viewed as a general exercise, we thought that mind concentration or heavy somatic awareness on body motions in 24TJQ exercise also contributed to inhibit alpha appearance or displayed an alpha-attenuation pattern, which resulted in high appearance of beta%-power instead.…”
Section: Discussionsupporting
confidence: 92%
“…By comparison with the alpha%-power to beta%-power, both groups showed high beta%-power during exercise and big increases of alpha%-power after exercise. This is basically consistent with other reports about the influence of exercise on alpha-beta wave (Petruzzello and Landers, 1994;Shibata et al, 1997). However, 24TJQ is viewed as a general exercise, we thought that mind concentration or heavy somatic awareness on body motions in 24TJQ exercise also contributed to inhibit alpha appearance or displayed an alpha-attenuation pattern, which resulted in high appearance of beta%-power instead.…”
Section: Discussionsupporting
confidence: 92%
“…The ␣ -wave increase after 24TJQ exercise corresponded well to the results of some previous studies, which reported an ␣ -wave increase after aquatic aerobics and walking exercises [14,18,19] . However, no changes in ␣ -wave were observed after ergometry exercise.…”
Section: Relationship Between Eeg Change and Poms T Scores Change Aftsupporting
confidence: 90%
“…This suggested that the cerebral cortex activity did not decrease or become calm immediately after 24TJQ exercise (in the post1), but did become calm in the post2, which resulted in a relaxing effect on the mind and body [14] . Although occipital dominance of ␣ -wave is the ordinary pattern in normal psychological conditions, studies [15][16][17] have revealed that the wave will spread to the central and frontal regions, or appear simultaneously in the occipital region.…”
Section: Relationship Between Eeg Change and Poms T Scores Change Aftmentioning
confidence: 99%
“…The use of treadmills, in clinical and research settings [1][2][3][4][5][6], rests upon the assumption that reliable and valid measures of gait can be obtained during treadmill walking (TW) and that TW can be generalized to overground walking (OW). TW, in theory, is mechanically equivalent to OW, but in reality walking on a treadmill is initially an unfamiliar experience.…”
Section: Introductionmentioning
confidence: 99%